Vật liệu aluminosilicat mao quản trung bình từ cao lanh. II. Tổng hợp và đặc trưng vật liệu mao quản trung bình MSU-S có thành phần cấu trúc zeolit ZSM-5, beta trong môi trường kiềm - Hảo, Phạm Minh; Đôn, Tạ Ngọc; Yêm, Hoàng Trọng (Vietnam Journal of Chemistry, 2012)
Mesostructure aluminosilicate materials assembled from ZSM-5 (MFI), beta (BEA) zeolite seeds have synthesized successfully from metakaolin under basic medium. They were characterized by XRD, nitrogen adsorption isotherm, TEM, FTIR, TPD_NH3. The results exhibit character of the ordered hexagonal mesostructures assembled from ZSM-5, Beta zeolite seeds with the wall thickness of 8 Å, pore size of 38 Å, BET surface area of 723m2/g and 700 m2/g, respectively. These materials contain both strong and weak acidic sites.